Evolution of a Geothermal System with Fluid Re-Injection - Angiolo Farina; Antonio Fasano; Mario Primicerio; Fabio Rosso (Applied Sciences, 2020)
In this paper, we study the stationary configurations of a vapor-dominated geothermal system. We propose a general mathematical model, which turns out to be a free boundary problem, and we focus on the stationary solutions. The analysis, developed considering the data of the geothermal field in Larderello, Tuscany (Italy), shows that steady-stable states may exist both when the re-injection takes place in depth and when the natural recharge is distributed both in the area occupied by vapor and in the one occupied by liquid.